(untitled) (Research, Society and Development, 2021)
The ​Acquired Immunodeficiency Syndrome (AIDS) is a disease caused by the human immunodeficiency virus (HIV), which affects the human immune system by destroying the white blood cells, responsible for the defense of the body. Based on this problem, the present study aimed to describe the epidemiological profile of HIV/AIDS inpatients in Brazil. For this, an integrative literature review (ILR) research was developed. Twenty-three articles were selected, read in full, and used for data construction. The publications were organized in the following categories: sex predominance, transmission forms, age, marital status, level of education, occupational situation and associated pathologies. It was verified the increase in the number of cases of hospitalizations for HIV in Brazil, in addition to the predominance among single men, with low education level and active sexual life associated with the non-use of condoms.